Pengaruh Lingkungan Kerja dan Motivasi Kerja Terhadap Kinerja Pegawai pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kota Depok: Pendahuluan, Kajian Pustaka, Metode, Hasil dan Pembahasan, Pembahasan, Kesimpulan, Saran, Daftar Pustaka - Itsnaini, Maulida (Universitas Sumatera Barat, 2023)
BKPSDM is an institution responsible for formulating technical policies in the field of staffing and providing service support for governance in regional personnel management. An effort to improve employee performance is to create a conducive work environment that motivates employees to work better. The purpose of this study was to determine the effect of work environment on employee performance, work motivation on employee performance, and the effect of work environment and work motivation simultaneously on employee performance at BKPSDM Depok City. The data collection methods used are observation, interviews, and distributing questionnaires to 60 BKPSDM employees. This research method is quantitative statistics. The data analysis method used is multiple linear regression analysis. The results of this study indicate that Work Environment and Work Motivation have a positive and significant effect both partially and simultaneously on Employee Performance at BKPSDM Depok City with a correlation coefficient R Square of 0.410 or 41%. This proves that employee performance can be explained by 41% of the independent variables in this study, namely work environment and work motivation, the rest is explained by variables outside the independent variables in this study.